2020
DOI: 10.21071/edmetic.v9i1.12462
|View full text |Cite
|
Sign up to set email alerts
|

Marco Europeo de Competencia Digital Docente «DigCompEdu». Traducción y adaptación del cuestionario «DigCompEdu Check-In»

Abstract: La tecnología, como ingrediente fundamental para el avance de la Sociedad del Conocimiento, ha asumido un papel fundamental en el entorno educativo. En esta línea, diferentes instituciones y estudios científicos respaldan la importancia de la competencia digital docente dentro de los nuevos contextos de alfabetización. Este artículo persigue brindar un análisis objetivo y riguroso del concepto, estudiando el principal marco europeo de competencia digital docente «DigCompEdu». Además, también se presenta la tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0
20

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 106 publications
(97 citation statements)
references
References 1 publication
(1 reference statement)
1
45
0
20
Order By: Relevance
“…The European Union defines key competencies as "a combination of knowledge, capacities and attitudes adapted to the context" (Council of the European Union, 2018, p. 7). Being competent is related to everything that society requires to overcome the obstacles of the time in which it develops (Cabero-Almenara & Palacios-Rodríguez, 2019;Palacios-Rodríguez, 2020). In the so-called knowledge society, one of these fundamental competencies is digital competence, i.e., "that which involves the safe and critical use of information society technologies for work, leisure and communication" (Council of the European Union, 2018, p. 9).…”
Section: Introductionmentioning
confidence: 99%
“…The European Union defines key competencies as "a combination of knowledge, capacities and attitudes adapted to the context" (Council of the European Union, 2018, p. 7). Being competent is related to everything that society requires to overcome the obstacles of the time in which it develops (Cabero-Almenara & Palacios-Rodríguez, 2019;Palacios-Rodríguez, 2020). In the so-called knowledge society, one of these fundamental competencies is digital competence, i.e., "that which involves the safe and critical use of information society technologies for work, leisure and communication" (Council of the European Union, 2018, p. 9).…”
Section: Introductionmentioning
confidence: 99%
“…(a) Guarantee that the information obtained through the analysis and the different interpretations value the reality that is being measured. The first of the objectives (a) was achieved following a standardized procedure for the construction of this type of scales [6,19,[30][31][32][41][42][43]; which was included from developing preliminary versions (alpha versions), to obtaining a beta version that was subjected to a content analysis by a group of experts in educational technology. After applying the Likert-type scale of eight response options, the experts' report showed that almost all the items were written in a language appropriate to their recipients, that they met the objectives set out in their design and that they were assessed with the maximum score for its clarity of presentation.…”
Section: Discussionmentioning
confidence: 99%
“…To achieve the proposed objectives (b, c and d), different statistical tests were carried out as suggested by related studies [30][31][32]35]. The reliability, discriminant validity and convergent validity of the questionnaire were calculated using the coefficients: Cronbach's Alpha, McDonald's Omega, composite reliability (CR) and average variance extracted (AVE).…”
Section: Procedures and Data Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…El marco «DigCompEdu» también se usa como referencia en algunos programas autonómicos para la digitalización de centros educativos españoles como, por ejemplo, el proyecto andaluz #PRODIG (Consejería de Educación y Deporte, 2018). Al mismo tiempo, "DigCompEdu» es compatible con el Marco Común de Competencia Digital Docente, publicado por el INTEF, en sus distintas dimensiones y niveles (Cuartero, Porlán y Prendes, 2016;INTEF, 2017bINTEF, , 2017a.…”
Section: Digcompeduunclassified